2018
DOI: 10.1097/ajp.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intra-Articular Botulinum Toxin in Osteoarticular Joint Pain

Abstract: BT-A intra-articular injections have short-term benefits with a statistically significant decrease in the NRS pain score of around 1 point in patients with refractory joint pain. A decrease in the pain score was also observed at 6 months but with a nonsignificant result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Meta-analyses and systematic reviews have been published, summarizing these results [24,[30][31][32][33]. A meta-analysis of six randomized controlled trials using IA BoNT for osteoarticular pain, found a statistically significant, short-term one point decrease of a numerical rating scale (NRS) pain score, and a decrease at 6 mo that was not statistically significant [34]. An earlier meta-analysis, which included some of the same studies, found similar results [33].…”
Section: Clinical Use Of Botulinum Toxin For Arthritis Painmentioning
confidence: 90%
“…Meta-analyses and systematic reviews have been published, summarizing these results [24,[30][31][32][33]. A meta-analysis of six randomized controlled trials using IA BoNT for osteoarticular pain, found a statistically significant, short-term one point decrease of a numerical rating scale (NRS) pain score, and a decrease at 6 mo that was not statistically significant [34]. An earlier meta-analysis, which included some of the same studies, found similar results [33].…”
Section: Clinical Use Of Botulinum Toxin For Arthritis Painmentioning
confidence: 90%
“…114,145 Botulinum modulates neurogenic inflammation and reduces nociceptive stimulation. 146 Although animal studies suggested a potential effectiveness of botulinum on chronic pain associated with OA, 147 its effectiveness in patients with OA of the knee is not supported by strong scientific evidence. Indeed, in several studies botulinum does not differ from sham therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Courseau 32 in a systematic review and meta-analysis evaluated the efficacy of intra-articular injections of botulinum toxin A (produced by the anaerobic bacterium Clostridium Botulinum) in patients affected by painful osteoarthritis. Although many studies indicate that the botulinum toxin can reduce pain through the reduction of peripheral and central sensitization, in this meta-analysis no significant improvement was found in patients affected by hip or knee OA.…”
Section: Botulinum Toxin Type Amentioning
confidence: 99%